Pyruvate Dehydrogenase Activity Is Decreased in Emergency Department Patients With Diabetic Ketoacidosis. (17th February 2016) - Andersen, Lars W.; Berg, Katherine M.; Montissol, Sophia; Sulmonte, Christopher; Balkema, Julia; Cocchi, Michael N.; Wolfe, Richard E.; Balasubramanyam, Ashok; Liu, Xiaowen; Donnino, Michael W.
Abstract: Objectives: The pyruvate dehydrogenase complex (PDH) is an essential enzyme in aerobic metabolism. Ketones are known to inhibit PDH activity, but the extent of this inhibition is unknown in patients with diabetic ketoacidosis (DKA). Methods: We enrolled adult patients presenting to the emergency department in hyperglycemic crisis. Patients were classified as DKA or hyperglycemia without ketoacidosis based on laboratory criteria. Healthy controls were also enrolled. PDH activity and quantity were measured in isolated peripheral blood mononuclear cells. We compared PDH values between groups and measured the relationship of PDH values to measures of acid–base status. Results: Twenty‐seven patients (17 with DKA) and 31 controls were enrolled. Patients with DKA had lower PDH activity and quantity compared to the two other groups. PDH activity was significantly correlated with serum bicarbonate and pH and inversely correlated with the anion gap. Conclusions: DKA is associated with greater suppression of PDH activity than hyperglycemia without ketoacidosis, and this is correlated with measures of acid–base status. Future studies may determine whether PDH depression plays a role in the pathophysiology of DKA and whether modification of PDH could decrease time to DKA resolution.